An anonymized, de-identified registry study protocol to determine the effectiveness and safety of weight loss with enavogliflozin in patients with type 2 diabetes mellitus. - Hyunji Sang; Sunyoung Kim; Jiyoung Hwang; Selin Woo; Jaewon Kim; Dong Keon Yon; Sang Youl Rhee (PLoS ONE)
Sodium-glucose co-transporter 2 inhibitors, such as enavogliflozin, offer promising metabolic benefits for patients with type 2 diabetes (T2D), including glycemic control and improved cardiac function. Despite the clinical evidence, real-world evidence is needed to validate their safety and effectiveness. This study aims to evaluate the effects of weight loss and safety of enavogliflozin administration in patients with T2D in a real-world clinical setting over 24 weeks. This is a large-scale, prospective, multicenter, non-interventional observational study and will be conducted in 12 primary care centers nationwide between 2024 and 2026. Data will be collected at baseline, 12 weeks, and 24 weeks in a real-world clinical setting, including demographic details, clinical history, lifestyle habits, medication use, and various health indicators. Eligible participants are adults aged 19 to 80 with T2D and a body mass index (BMI) of ≥23 kg/m2 who are currently receiving treatment with Envlo (enavogliflozin) or Envlomet (enavogliflozin/metformin) tablets or planning to start treatment. The primary outcome is the change in BMI and body weight at 24 weeks from baseline. Secondary outcomes evaluated are changes in BMI and weight at 12 weeks, the proportion of participants achieving significant reductions in BMI and weight at 12 and 24 weeks, and body composition and glycemic improvements at 12 and 24 weeks. The study will analyze shifts in lipid profiles, liver and kidney functions, and body composition at 12 and 24 weeks as exploratory outcomes. For safety outcomes, the trial will prioritize the monitoring of adverse drug reactions and specific events of interest such as hypoglycemia, urinary tract infections, genital infections, polyuria, and polydipsia. This study design enables us to evaluate the effectiveness and safety of enavogliflozin for weight loss in a real-world setting while exploring its potential positive effects on cardiac function and metabolic risk factors in overweight or obese patients with T2D.